Lack of Correlation of Plasma HDL With Fecal Cholesterol and Plasma Cholesterol Efflux Capacity Suggests Importance of HDL Functionality in Attenuation of Atherosclerosis - Srivastava, Neelam; Cefalu, Angelo B.; Averna, Maurizio; Srivastava, Rai A. K. (Frontiers in Physiology, 2018)
To circumvent the residual cardiovascular disease burden in patients receiving statin therapy, VA-HIT findings suggested HDL-raising as a plausible approach. However, lack of benefits of cholesterol ester transfer protein (CETP) inhibitors despite substantial increase in HDL and reduced cardiovascular disease (CVD) risk among apoA-I Milano subjects with low HDL, shifted the focus from HDL level to HDL function. We employed both radioisotopic and non-radioisotopic methods to quantitate fecal cholesterol as measure of HDL functionality. Using this method, we carried out studies in C57Bl, apoA-I-Tg, ob/ob, and LDLr-deficient mice using reference agents, LXR and PPAR-α agonists, known to modulate HDL. In C57Bl mice, LXR agonist, T1317, raised HDL by 30%, while PPAR-α agonist, fenofibrate, decreased HDL by 30%, but fecal cholesterol showed 2-fold increase in both cases. Interestingly, combination of LXR and PPAR-α agonists showed no change in HDL concentration, but fecal cholesterol increased by 4.5-fold. In apoA-I-Tg mice, HDL increased by 40%, 80%, and 80% in LXR, PPAR-α, and combination treatments, respectively; fecal cholesterol increases were 1.8, 1.8, and 5-fold, suggesting a lack of correlation between HDL level and fecal cholesterol. Similarly, HDL level and fecal cholesterol lacked correlation in hyperlipidemic diabetic ob/ob mice treated with HDL modifying agents. Atherosclerosis attenuation by LXR and PPAR-α agonists in LDLr-deficient mice was associated with increased fecal cholesterol, but not HDL level. These data suggest: a) a lack of correlation between HDL level and fecal cholesterol; b) LXR and PPAR-α agonists enhance RCT synergistically; and c) reduced aortic lipids were associated with increased fecal cholesterol.